2010
DOI: 10.4103/0974-7753.77510
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic alopecia: Quality-of-life and associated lifestyle patterns

Abstract: Background:Androgenetic alopecia (AGA) is a condition, which is an important psychosocial problem. The hormonal variations causing AGA are known, but whether behavioral patterns and lifestyle influence the condition and which age groups they influence is uncertain and such factors have not been studied in detail.Objectives:To compare association of lifestyle patterns with androgenetic alopecia, prevalence of psychiatric symptoms and resulting quality-of-life (QoL) between two age groups of males with AGA.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
4
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 15 publications
2
57
4
9
Order By: Relevance
“…In a study older patients were more severely afflicted for subscales of functioning, stigmatization and symptoms whereas emotional score was more severely affected in young population. 20 In our study, older subjects had more severe symptoms. Similar to our findings, Neena et al 20 also found symptom score to be more in the older age group as compared with younger individuals.…”
mentioning
confidence: 66%
“…In a study older patients were more severely afflicted for subscales of functioning, stigmatization and symptoms whereas emotional score was more severely affected in young population. 20 In our study, older subjects had more severe symptoms. Similar to our findings, Neena et al 20 also found symptom score to be more in the older age group as compared with younger individuals.…”
mentioning
confidence: 66%
“…Also increasing hours of cap wearing among males with androgenic alopecia showed decrease in interest to seek medical treatment (p=0.001) which implies that wearing a cap for a longer period of time helps to ward off the social stigma and the psychological effects of alopecia in them. This study serves as a baseline to help physicians understand the effects on quality of life in patients with androgenic alopecia as well as in prescribing cap wearing for them on a long term daily basis [25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…El cuestionario Hairdex ® es una herramienta muy utilizada en este sentido, y consta de 48 preguntas de respuesta múl-tiple que valoran el estado emocional, la función, los síntomas, la seguridad en uno mismo y la estigmatización. Otra herramienta común es el Symptom Check List-90-R (SCL-90-R), un instrumento de cuantificación sintomática que permite medir la intensidad de 90 síntomas psicológicos y psicopatológicos 10 . Los cuestionarios Dermatology Life Quality Index (DLQI), Short Form-36 Health Survey (SF-36) y Skindex-29 fueron desarrollados para evaluar la calidad de vida en los problemas de la piel, pero también se utilizan en la alopecia ante la escasez de escalas específicas en este campo 11 .…”
Section: Epidemiología E Impactounclassified